ANALISIS LANGKAH-LANGKAH PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN FISIKA - Dehong, Rosinta; Kaleka, Melkyanus Bili Umbu; Rahmawati, Ana Silfiani (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
This study aims to analyze the steps of applying the discovery learning model in physics learning. This type of research is qualitative with the type of case study. The subjects in this study were physics teachers and students of class X SMKN 2 Ende, totaling 33 students. The object of this research is the application of the discovery learning model. Data collection instruments using questionnaires and documentation. Data were analyzed descriptively. The results showed that the application of the discovery learning model in physics learning for class X students of SMK Negeri 2 Ende was in accordance with the syntax. The syntax of the discovery learning model consists of stimulation, problems, data collection, data processing, verification, generalization.